Relationship between Business Competency and Employee Performance Improvement: A Study of Nepalese Banking Sector (Pravaha, 2020)
This study describes the employees’ business competency and performance improvement and their relationship on the basis of responses collected from selected commercial banks inside Kathmandu valley. The main objective of this study was to analyze the employees’ perception on business competency and performance improvement in the banking industry of Nepal.This study adopted a descriptive and comparative design. The size for the research were 210 respondents. Primary data were collected from employee working in banks through a set of a structured questionnaire for the research. To analyze the collected data, mean, standard deviations and Pearson correlation analysis were conducted to identify the relationship between independent variables (Business competency) and dependent variable (Employee performance improvement. This research conformed that Nepalese employees in banking sector are aware of business competency and performance improvement. There is a strong correlation between employees’ business competency and performance improvement.